Behaviour of Catalytic Oxidation of Dilute Combustible Gas in a Jacketed Fixed Bed Reactor Under Flow Reversal Process. - Perpustakaan UGM, i-lib ([Yogyakarta] : Center For Food and Nutritions Studies Gadjah Mada University, 1999)
An experimental study of the catalytic oxidation of combustible gas in air has been made under flow reversal operation. The experiments were done using a three-zone reactor consisting of two beds packed with an inert having high heat capacity solid placed at both ends of a bed packed with catalyst. The catalyst bed was cooled by passing a fluid through a jacket surrounding the bed. The influence of the operating parameters upon the shape of temperature profiles, percent conversion and heat removal through the coolant were studied. The experiments showed that the maximum measured reactor temperature and heat removal were insensitive to changes in cycle duration and initial temperature but sensitive to feed flow rate and changes in reactant concentration.